Implementing advance care planning in heart failure: a qualitative study of primary healthcare professionals - Schitel, M; Macartney, J; Wee, B; Boylan, A-M (Royal College of General Practitioners, 2021)
Background: Advance care planning (ACP) can improve the quality of life of patients suffering from heart failure (HF). However, primary care healthcare professionals (HCPs) find ACP difficult to engage with and patient care remains suboptimal.